From presumed benign neck masses to delayed recognition of human papillomavirus–positive oropharyngeal cancer. (5th April 2019) - Davis, Ruth J.; Rettig, Eleni; Aygun, Nafi; Rooper, Lisa; D'Souza, Gypsyamber; Eisele, David W.; Fakhry, Carole
Abstract : Objectives/Hypothesis: To describe patients with delayed diagnosis of human papillomavirus–positive oropharyngeal squamous cell carcinoma (HPV‐OPC) after initial incorrect diagnosis of branchial cleft cyst or nondiagnostic workup of unilateral neck mass. Study Design: Retrospective case series. Methods: Patients with delayed diagnosis of HPV‐OPC after initial nondiagnostic workup for unilateral neck mass were eligible. Medical record abstraction was performed to describe clinical characteristics at initial presentation and later diagnosis of HPV‐OPC. To estimate nodal growth rates, the short axis diameter of the lymph nodes was determined from imaging reports. Results: Six patients met eligibility criteria. After a median interval of 42 months (range, 3 months–7 years) from initial presentation with unilateral neck mass, patients were diagnosed with HPV‐OPC. At the time of HPV‐OPC diagnosis, five were AJCC eighth edition overall stage I, and one was stage II. Primary tumors were T0 or T1 in the majority (83.3%, n = 5). Among five patients with available serial imaging, despite diagnostic delay, three of five still had a single lymph node without involvement of additional nodes, whereas the remaining two developed additional suspicious nodes (ipsilateral and contralateral). Two of five developed evidence of extranodal extension. Median lymph node growth was 9.5% per year (range, −6% to 32%). Conclusions: Although the natural history of HPV‐OPC is not well understood, this case series suggests that it can be slow growing and mimic benign processes, leading to diagnostic delays. Adults presenting with neck masses should undergo complete diagnostic evaluation. Level of Evidence: 4 Laryngoscope, 130:392–397, 2020